Culture, Leadership, and Commitment for Enhancing Organizational Citizenship Behaviour: Evidence from Civil Servant Teachers - Anggraeni, Venita; Rubini, Bibin; Irdianysah, Iyan (Edukasi, 2025)
This study examines the relationships among organizational culture, effective leadership, and work commitment in predicting teachers' Organizational Citizenship Behavior (OCB) in A-accredited public senior high schools in Bogor Regency, Indonesia. The research addresses a critical gap in understanding how these factors collectively influence teachers' discretionary behaviors amid educational transformation challenges. A quantitative correlational design was employed, with data collected from 128 civil servant teachers (PPPK) across 13 schools using validated questionnaires. Reliability coefficients exceeded 0.70 for all instruments. Simple and multiple regression analyses were conducted to examine individual and collective effects. The findings revealed that organizational culture demonstrated the strongest individual effect on OCB (R² = 0.310, r = 0.557, p < 0.001), followed by work commitment (R² = 0.132, r = 0.363, p < 0.001) and effective leadership (R² = 0.101, r = 0.317, p < 0.05). However, in the multiple regression model, organizational culture emerged as the only statistically significant predictor (β = 0.251, p < 0.001), while effective leadership (p = 0.061) and work commitment (p = 0.358) became non-significant. The three variables collectively explained 33.7% of OCB variance (R² = 0.337, F = 21.027, p < 0.001), suggesting that organizational culture functions as the primary mechanism through which leadership and commitment influence teachers' discretionary behaviors. These findings indicate that strengthening organizational culture should be the primary strategy for enhancing teacher OCB, with leadership development and commitment-building serving as complementary approaches. The study contributes empirical evidence to organizational behavior theory in educational contexts and provides actionable guidance for enhancing teacher performance and organizational effectiveness.